STABILIZATION OF RED MELINJO PEEL (GNETUM GNEMON L.) ETHYL ACETATE EXTRACT AS ANTIBACTERIAL AGENT - Honga, Johan; Parhusip, Adolf J.N.; Anugrahati, Nuri A.; Sinaga, Wenny S.L.; Angel, Veliana (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2019)
Melinjo (GnetumgnemonL.) is a typical Indonesian plant that has many benefits such as antimicrobial agent. The aim of this study was to determine the antimicrobial activity of red melinjo peel extract. In this study, extraction was conducted by maceration using ethyl acetate as solvent for 24 hours at room temperature. 4-16% red melinjo peel extract (w/v) could inhibit the growth of Staphylococcus aureusATCC 6538, Listeria monocytogenesATCC 7644 and SalmonellaTyphi ATCC 14028. However 4-16% red melinjo peel extract could not inhibit the growth of Candida albicansATCC 10231. In stability test, the selected extract had a stable inhibition at pH 4-7, heat treatment 65oC-95oC for 30 minutes, salt 1%-5%, and sugar 10%-50%. The selected extract produced the biggest inhibition diameter at low pH (pH 4) and produced the smallest inhibition diameter at neutral pH (pH 7). Heat treatment 65oC for 30 minutes produced the biggest inhibition diameter among tested bacteria and decreased with increasing heating temperature. Addition of 1-5% NaCl and 10-50% sucrose worked synergistically with the selected extract in inhibit the growth of the tested bacteria.